Implementation of information technology utilization in improving the service quality of Kring Pajak - Jawahir, Irvan; Tristiyanti, Rahayu; Wijayanti, Tri; Dahlifah, Dahlifah; Zulfiati, Lies (Educoretax, 2025)
This study aims to analyze the implementation of the use of information technology in improving the quality of tax kring services.in improving the quality of Tax kring services. The method used is descriptive qualitative. Data collection is done by means of triangulation, namely using various data collection techniques such as interviews, observation, and documentation. Interviews were conducted to obtain understanding directly from informants related to the use of information technology, while observation aims to see the process of Kring Pajak service directly. process directly. Interviews were conducted with two main groups, namely Kring Pajak employees and taxpayers who have used the service. Kring Pajak employees and taxpayers who have used this service, with a focus on user experience, information technology system performance, and feedback. user experience, information technology system performance, and suggestions for improvement. for improvement. The duration of the research period was from October 2024 to Janaury 2025. Research results The results show that the implementation of information technology has significantly improved the quality of service to taxpayers, both in terms of ease of access and employee operational efficiency. For Kring Pajak employees, information technology information technology facilitates administrative tasks through automation systems, such as recording tax complaints. recording tax complaints. This research also found several challenges, including limited technological literacy among certain taxpayers, particularly from the older among certain taxpayers, especially from the older age group, as well as technical constraints in the form of slow slowness of the system when many users access it simultaneously. Directorate of Directorate General of Taxes (DGT) needs to improve the information technology infrastructure that supports the Kring Pajak service. supporting the Kring Pajak service.